Cytokinesis During the First Division of a Mouse Embryo - Fan, Xiao-Yan; Wang, Xing-Hua; Xie, Feng-Yun; Ma, Jun-Yu; Ou, Xiang-Hong; Luo, Shi-Ming (Frontiers in Cell and Developmental Biology, 2022)
Cell division consists of nuclear division (mitosis for somatic cells and meiosis for germ cells) and cytoplasmic division (cytokinesis). Embryonic developments are highly programmed, and thus, each cellular event during early embryo development is stable. For mouse embryos, the first time of mitosis is completed about 22 h after fertilization. However, it remains unclear when the embryo completes its first cytokinesis. Here, we microinjected only one cell in the 2-cell stage mouse embryos with mRNA, which encodes green fluorescence protein (GFP). By monitoring the GFP protein transport dynamics between the two cells, we demonstrated that the first time of cytokinesis in mouse embryos is completed about 15 h after mitosis, namely 37 h after fertilization. In addition, our results indicate that the cytoplasmic protein transport between daughter cells is very effective, which relies on microtubules instead of microfilaments in 2-cell mouse embryos. These results should enrich people’s understanding of the first cell division and cytoskeleton in mouse embryos and then learn more about the mechanisms of early embryo development in mammals.